101k views
5 votes
If f(x)=-x^2+6x-1 and g(x) =3x^2-4x-1, find (f-g)(x)

User Mattbawn
by
6.0k points

2 Answers

1 vote

Answer:

(f-g)(x) = -4x^2 + 10x - 2

Explanation:

Writing f(x) first and then writing g(x) beneath it may make this problem a bit easier to understand:

f(x)= -x^2+6x -1

-g(x) = -3x^2+4x -1

-----------------------------

(f-g)(x) = -4x^2 + 10x - 2

User Tymek
by
5.8k points
6 votes

Answer:


Explanation:

Given,


f(x)=-x^(2) +6x-1\\g(x)=3x^(2) -4x-1

we know,

(f-g)(x)=f(x)-g(x)

So, here we get

(f-g)(x)

=f(x)-g(x)

=
-x^(2) +6x-1-(3x^(2) -4x-1)

=
-x^(2) +6x-1-3x^(2) +4x+1

=
-x^(2)-3x^(2) +6x+4x-1+1

=
-4x^(2) +10x

So, the answer is


-4x^(2) +10x

User Ospho
by
6.4k points